Perencanaan Distribusi Gas LPG 3 kg Menggunakan Metoda Distribution Requirement Planning (DRP) di PT Anugrah Ditamas Lestari - Suryana, Hendy; Faruk, Umar (Jurnal Media Teknik dan Sistem Industri, 2017)
Gas is a contributing factor in various industrial and household activities. PT Anugrah Ditamas Lestari is one of the 3kg lpg gas agent that was established since 2008. The problem that happened in PT Anugrah Ditamas Lestari is that lpg gas sales will be hampered and can not be done in a timely manner will eventually cause loss. Forecasting Linear Regression starts from January 2015 to December 2016, while the DRP (distribution requirement planning) applied in research in gas agents is to know the needs for each base it can be known from the value of gross requirement. the need for a hilman base in 2016 is 63728 tubes / year, Asep.R 58898 tubes / year, Dedin 59961 tubes / year, Didin 58524 tubes / year, muhyidin 8771 tubes / year, suherman 77919 tubes / year, Haris 60108 tubes / year , Ujang 62964 tube / year, Irfan 54095 tube / year while for the maman base of 56826 tubes / year.Â As for knowing the needs and determining the delivery of lpg gas to each base can be seen from the calculation of pland order release, for the Hilman base it needs a gas supply of 63700 tubes / year, while for Dedin 58900 tubes / year, Didin 59800 tubes / year, muhyidin 8700 tubes / year, suherman 77800 tubes / year, Haris 59900 tubes / year, Ujang 62500 tubes / year Irfan 53600 tube / year, while for the maman base needs lpg gas supply of 56800 tubes / year calculation of DRP needs lpg gas most is suherman base as much as 77800 tubes / year.Keywords: linear regression forecasting, DRP (Distribution Requirement Planning) gross requitment and Plannd order releaseÂ